2012
DOI: 10.1186/1471-2164-13-309
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctionality and diversity of GDSL esterase/lipase gene family in rice (Oryza sativa L. japonica) genome: new insights from bioinformatics analysis

Abstract: BackgroundGDSL esterases/lipases are a newly discovered subclass of lipolytic enzymes that are very important and attractive research subjects because of their multifunctional properties, such as broad substrate specificity and regiospecificity. Compared with the current knowledge regarding these enzymes in bacteria, our understanding of the plant GDSL enzymes is very limited, although the GDSL gene family in plant species include numerous members in many fully sequenced plant genomes. Only two genes from a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
167
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(176 citation statements)
references
References 90 publications
6
167
0
Order By: Relevance
“…4) This family consists of many members with such diverse functions as ceramidase, 5) sinapine esterase, 6) transesterification, 7) cutin synthesis 8) and cutinase activities 9) in plants. 10) We confirmed that the recombinant enzyme expressed in Escherichia coli as a fusion with maltosebinding protein (MBP) showed acyltransferase activity for pyrethrin synthesis. The enzyme displayed high substrate specificity for the acid and alcohol moieties, recognizing the absolute configuration of the three asymmetric carbons in the substrates.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…4) This family consists of many members with such diverse functions as ceramidase, 5) sinapine esterase, 6) transesterification, 7) cutin synthesis 8) and cutinase activities 9) in plants. 10) We confirmed that the recombinant enzyme expressed in Escherichia coli as a fusion with maltosebinding protein (MBP) showed acyltransferase activity for pyrethrin synthesis. The enzyme displayed high substrate specificity for the acid and alcohol moieties, recognizing the absolute configuration of the three asymmetric carbons in the substrates.…”
mentioning
confidence: 53%
“…4) GDSL lipases/esterases generally contain serine in Block I, glycine in Block II and asparagine in Block III, as well as aspartate and histidine in Block V as the amino acids involved in hydrolase activity. 10,11) Histidine in Block V deprotonates serine in Block I with the assistance of aspartate in Block V, and activated serine attacks the carbonyl carbon of substrates in the ''catay To whom correspondence should be addressed. Tel: +81-742-43-7153; Fax: +81-742-43-1445; E-mail: kmatsuda@nara.kindai.ac.jp Abbreviations: TcGLIP, Tanacetum cinerariifolium GDSL lipase/esterase; MBP, maltose-binding protein; SDS-PAGE, sodium dodecyl sulfatepolyacrylamide gel electrophoresis lytic triad.''…”
mentioning
confidence: 99%
“…GDSL lipases represent a subfamily of lipolytic enzymes that show very broad substrate specificity (Chepyshko et al, 2012).…”
Section: A Possible Mechanism Contributing To Seed Germinationmentioning
confidence: 99%
“…GDSL lipases/esterases are known for their broad regio-and substrate specificity. More than 100 members of this enzyme group have been identified in the Oryza sativa genome (Chepyshko et al 2012). The native CGT from tomato was purified to near homogeneity and used for protein sequencing.…”
Section: Lipase-like Hydroxycinnamoyltransferasesmentioning
confidence: 99%